Psychological care of caregivers, nurses and physicians: a study of a new approach. (4th January 2014) - Abeni, Maurizio S.; Magni, Margherita; Conte, Martina; Mangiacavalli, Silvia; Pochintesta, Lara; Vicenzi, Gaia; Ferretti, Virginia V.; Pompa, Alessandra; Cocito, Federica; Klersy, Catherine; Corso, Alessandro
Abstract There is much evidence demonstrating that psychosocial interventions in caregivers and oncological staff produce an improvement in their patients' quality of life. The aim of this explorative study was to evaluate the effect of a new approach in promoting more functional ways to face stressful situations in the constellation of people around patients: caregivers, physicians and nurses. Thirty‐four subjects were divided into three groups: 10 caregivers, 11 physicians, and 13 nurses. A "Balint Group" method modified according to a mindfulness technique was used as the intervention. Three assessment tools were administered to the participants at baseline, during, and after completion of the study: the Response Evaluation Measure (REM‐71), the Satisfaction Profile (SAT‐P), and the Group Climate Questionnaire (GCQ). Mean values of defense mechanisms determined by the REM‐71 were compared with those of the standard population. At baseline, we observed a prevalence of immature defenses in the three groups, with mean values above those in the standard population. After the psychological intervention, a tendency to normalization of the mean values was observed, indicating the development of more adaptive ways of using defense mechanisms and the effectiveness of the intervention. Group climate, assessed through the GCQ, showed an increase in the "Engagement" factor and a decline in the "Conflict" factor in all groups. This study suggests that group treatment focused on changing personal responses to stressful situations can induce more adaptive strategies enabling caregivers, hematologists, and nurses to help patients better and thereby improve their quality of life.